Analysis of Gayo Poet Traditional Communication Media In Building Community Islamic Insights Central Aceh District - Abdullah, Yusnadi, Salman Yoga S (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study aims to determine the Analysis of Gayo Poet Traditional Communication Media In Building Community Islamic Insights Central Aceh District by using qualitative research methods using data collection techniques such as Observation, Documentary, and Interview. The data that has been collected, compiled systematically, then read, translated, understood, and classified based on the coding that has been determined. Furthermore, explore and analyze the data carefully and take into account other appropriate references. The results of the research are that the "saer" poem in the Gayo community in Central Aceh Regency not only acts as a medium and means of art, but has a broad role and function in social life. The message and Islamic insight of Gayo's verse "saer" is an interpretation of Islamic religious teachings sourced from the Qur'an, the prophet's hadith and local wisdom of the community. The themes contained in the "saer" Gayo poem include the theme of Islamic teachings which include the value of monotheism, prayer and mu'amalah worship, pilgrimage, morals, alms, fasting, morals and education themes, Islamic history, the history of the Revolution. Independence of the Republic of Indonesia, local history, natural and environmental themes and cultural-customary themes.